1994
DOI: 10.1177/019372394018004003
|View full text |Cite
|
Sign up to set email alerts
|

“Buzzer Beaters” and “Barn Burners”: The Effects on Enjoyment of Watching the Game Go “Down to the Wire”

Abstract: Prior research on the effects of being kept in suspense about the outcome of a sports contest on spectators' enjoyment of the sporting event has yielded ambiguous findings, which the present investigation was designed to clarify. A high school football game was videotaped professionally. The tapes were edited, and play-by-play and color commentary was added, so as to create a suspenseful version and a nonsuspenseful version of the game. In addition to suspense, outcome of the game (favorable, unfavorable) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…Though these studies did not directly measure suspense or perceived suspense, it is clear that the way sporting events are described by commentators plays a role in how viewers perceive and experience the action. In the one study that did examine this relationship directly, Bryant, Rockwell, and Owens (1994) found that commentary provided by a partisan (i.e., hometeam) radio announcer can indeed add to the level of suspense experienced during the game by listeners who share that partisanship.…”
Section: Previous Conceptualizations Of Suspense Within Mediated Sportsmentioning
confidence: 99%
“…Though these studies did not directly measure suspense or perceived suspense, it is clear that the way sporting events are described by commentators plays a role in how viewers perceive and experience the action. In the one study that did examine this relationship directly, Bryant, Rockwell, and Owens (1994) found that commentary provided by a partisan (i.e., hometeam) radio announcer can indeed add to the level of suspense experienced during the game by listeners who share that partisanship.…”
Section: Previous Conceptualizations Of Suspense Within Mediated Sportsmentioning
confidence: 99%
“…The same is true of televised sporting events (Bryant, Rockwell, & Owens, 1994). Sports contests naturally contain dramatic elements, such as competition and violence.…”
Section: Investigating Suspense As a Predictor Of Enjoyment In Sportsmentioning
confidence: 96%
“…Bryant et al (1994) created suspenseful and non-suspenseful versions of a high school football game. The researchers found that viewers in the suspenseful conditions enjoyed the game more, and found the game less boring and more exciting.…”
Section: Suspense and Excitation Transfer Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Since previous research has shown games which have more suspense are more enjoyable to viewers, the clips edited together highlighted the closeness of the scores, and the slim margins of victory which occurred (Bryant, Rockwell, & Owens, 1994;Gan, Tuggle, Mitrook, Coussement, & Zillmann, 1997). Though the outcomes of the four different videos were different, the main elements of the videos remained as similar as possible.…”
Section: Video Four Featured Negative Commentary About the United Stamentioning
confidence: 99%